Romanian Transnational Families Gender, Family Practices and Difference - Ducu, Viorela (Springer International Publishing, 2018)
This book explores novel aspects of transnational family research through the study of Romanian transnational families. A range of topics are covered, including the impact of lodging type upon life strategies; understudied elements in transnational relationships; gender roles in transnational communication; multinational relationships; the role of polymedia in the formation of couples; and the lives of the children of Romanian transnational families. The author presents the experiences of 'leavers' as well as of 'stayers'; of the 'highly-skilled' as well as the 'low-skilled'; that of women and that of men - through individual testimonies and couple interviews. Romanian Transnational Families will be of interest to students and scholars across a range of disciplines, including sociology, politics, anthropology and geography. Chapter 3 and Chapter 5 of this book are available open access under a CC BY 4.0 license at link.springer.com .